Study Technology Purse seine and Operasion In The Village Of Aek Manis Sibolga North Sumatra Province - Irwan Limbong; Arthur Brown; Bustari ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted in December 2013, which is located in the village of Aek Manis Sibolga of North Sumatra Province. The research method used is a survey/diretc observation. The purpose of this study is to compile information about the technical aspects, economic, operation, environmental and purse seine that operated fisherman at Aek Manis village. The result of this research known that purse seine operated in the village of Aek Manis has the same technical aspects of generally construction with other purse seine which is comprised of the head rope, ground rope, body, wings , floats, sinkers, rings, Selvedge, purse line. The operation of purse seine is divided into three stages namely, Searching of fishes schooling, setting, and hauling. While the economic value of Rp 648.380.000, gross income, net income of Rp 145.770.000/year , benefit cost ratio (BCR) of 1.29 , financial rate return (FRR) is 61 %, payback period of capital (PPC) is 1.6. The rating value is 24.66 that means purse seine can be classified into environmental friendly fishing gear.Keywords: technical aspects,economical,operation, friendly environmentalfishing gear.